Diseño y construcción de un prototipo para la clasificación pitahaya amarilla por tamaño en la finca La Perdomo de la Plata (Huila) (2023)
The production of yellow pitahaya is increasingly gaining ground as an exotic fruit for export in Colombia; here the target markets have as a criterion the size of the fruit, which is why in the field days this activity is done manually leading to errors in the classification processes, which are evidenced by the rates of return by size, which in the Finca La Perdomo is 4.7% of the total production; to adjust this deviation, the construction of a yellow pitahaya sorting machine by size was proposed; For its development, this project was planned in stages, starting with the criteria defined by the producer, design of the prototype, construction and evaluation of the machine; The results showed that the sizes to be classified are larger and smaller than 8 cm, which are selected from a circular device or hopper which by slow centrifugal movement allows the selection inside the prototype, this operates with a motor of 0.25 Hp and its payload is 80 kg including the weight of the reducer, it is concluded that at design level the conditions of maximum force are met, since this value is 16.59 Mpa and the maximum displacement is a maximum of 0.36 mm. 36mm; according to the safety factor, the machine does not represent a risk of shearing in any of the components.